Penerapan Forecasting pada Kebutuhan Bahan Baku “Solven S 602” - Aries Aries; Hartiwi Prabowo; Teguh Sriwidadi; Ridho Bramulya Ikhsan (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
The problems in this research are fluctuating market demand conditions, sources of raw materials mostly from overseas so that they have a long order period, specialty raw materials so there are not many suppliers that sell similar raw materials. This study aims to find out how forecasting calculations at PT XYZ when using moving average methods, exponential smoothing, and linear regression. Processing data using Quantitative Method for Windows software (QM for Windows). The results showed that the forecasting of “Solven S 602” raw materials with the moving average method resulted in an average percentage of absolute errors of 3.448%; forecasting with the exponential smoothing method produces an average percentage of absolute errors of 4.951%; forecasting with linear regression method produces an absolute percentage error of 0% on average. The most appropriate forecasting method for PT. XYZ is a linear regression method because the absolute error is the smallest.